Management in Education: Competitiveness and Above-Professional Approach - E. V. Aleksandrova; R. A. Iskandaryan; D. M. Mayakov (Вестник Российского экономического университета имени Г. В. Плеханова)
To study the whole range of problems that should be resolved in the process of innovation management in education it is necessary to realize that teaching is flexible, supple and requires continuous research. The goal of the article is to corroborate rightness of theoretical vectors by permanently changing practice. Theoretical and methodological foundation of the step-by-step research presented in the article is formed by principles of economic and comparative analysis, methods of induction and deduction and finally the method of archive search. The authors proposed an innovation approach to achievements in the field of education and showed the efficiency of Russian experience of well-known economists and experts in economics, psychology and sociology.